Game development with Unity - Menard, Michelle (Boston, MA : Course Technology, 2012)
Game Development With Unity shows readers how to use the Unity game engine, a multiplatform engine and editor in one, to build games. Perfect for new developers or those looking to create games with an easy, efficient, and inexpensive game engine, they'll find a complete overview of the Unity editor along with basic game and level design theory taught alongside so they can build their game development skill set. New concepts and skills are taught using step-by-step tutorials and questions, as well comprehensive projects. Game Development With Unity covers everything from building game assets, to adding interactivity, to polishing your finished game and publishing it.
Includes index.
Keywords: Computer games -- Design; Computer games -- Programming; Video games -- Design